Implememtasi Permendikbudristek Nomor 55 Tahun 2024 Tentang Pencegahan Dan Penanggulanagan Kekerasan Di Lingkungan Perguruan Tinggi Di Universitas Lampung - Laila Fatia Maharani; Lanang Maulana; Komang Winda Sari; Sinta Bela Farah Kirani; Abdul Halim (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2026)
Violence in higher education institutions is a serious problem affecting students' psychological, academic, and social well-being. This study aims to examine the implementation of Permendikbudristek Number 55 of 2024 on the Prevention and Handling of Violence in Higher Education, specifically at Universitas Lampung. Using a qualitative descriptive approach, data were collected through interviews with students and members of the PPKPT Task Force. The findings indicate that the PPKPT Task Force at Universitas Lampung has carried out its prevention, handling, and victim protection functions; however, students' understanding of the reporting mechanism remains low. More intensive and sustained socialization is needed to optimize policy implementation and achieve a safe, inclusive, and violence free campus environment.